Clitics in imperative: proclisis, enclisis and mesoclisis in Albanian and in Italo-Romance varieties of Lausberg area - Baldi, Benedetta; Savoia, Leonardo M. (LingBaW. Linguistics Beyond and Within, 2020)
The relation between morpho-syntactic structure and its externalization into interpretive levels is the topic of this article. In many languages, typically in Romance and Albanian varieties, modal contexts, specifically imperative and infinitive, and negation, give rise to phenomena of clitic reordering and an interesting micro-variation. Imperative differs from declarative sentences in selecting enclisis except in negative contexts. Moreover, in Albanian mesoclisis appears in the 2nd plural person of imperative, between the verbal base and the person inflection. A similar distribution characterizes Calabro-Lucanian varieties spoken in Lausberg area, in contact with Arbëresh (Italo-Albanian) dialects. This article proposes to analyze the influence of modal contexts on the lexicalization of object clitics (OCls) and their different behavior in connection to their referential properties. Our descriptive and theoretical starting point is the representational morpho-syntactic approach adopted in Manzini and Savoia (2011 and subsequent works; see Section 5).